Assessing Intentions to Select Chengdu as a Sports Tourism Destination: Role of Perceived Value and Destination Image of Sports Events - Chunyang Yu; Li Xu; Hao Zhu; Songyu Jiang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The study investigates the factors influencing decision-making intentions for sports tourism destinations, employing the theoretical frameworks of perceived value and destination image. Utilizing an online survey and purposive sampling methodology, researchers obtained 417 valid questionnaires from tourists with experience in sports tourism in Chengdu. The collected data were subsequently analysed employing structural equation modelling techniques. Functional value, social value, and emotional value—representing the three dimensions of perceived value—positively impact attitudes and intentions toward sports tourism in Chengdu. Furthermore, the perceived destination image of sports events, encompassing both cognitive and affective aspects, exerts a comparable influence. Additionally, attitude toward sports tourism functions as a significant mediator in this relationship. This research contributes to the theoretical development of perceived value and perceived destination image within the context of sports tourism decision-making. The results provide crucial recommendations for Chengdu to bolster its sports tourism sector.